Rwanda Economic Update, No. 6 : Unearthing the Subsoil - World Bank Group (Washington, DC, 2014)
The Rwanda economic update reports on and synthesizes recent economic developments and places them in a medium-term and global context. It analyzes the implications of these developments and policies for the outlook of Rwanda s economy. These reports attempt to make an analytical contribution to the implementation of Rwanda s national development strategy. Each edition of the report includes a special feature on a selected topic. The report is intended for a wide audience, including policy makers, business leaders and other market participants, and the community of analysts engaged in Rwanda s economy.